Mateřská škola Domino - Remeš, Dominik (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce „Mateřská škola Domino“ je zpracována ve formě projektové dokumentace pro provedení stavby. Mateřská škola je navržena pro 24 dětí, součástí objektu je i rozlehlá zahrada. Jedná se o samostatně stojící objekt se dvěma nadzemními podlažími. Okolní terén je mírně svažitý. Mateřská škola se nachází v dobré docházkové vzdálenosti od obytných staveb ve Šlapanicích. Provoz tvoří 2 oddělení, technická část, část vedení, část zájmových činností. Jedná se o zděnou budovu založenou na základových pasech.

This final thesis "Kindergarten Domino" was made as a project documentation for a building construction. The kindergarten is designed for 24 children. Kindergarden is designed as a detached building consists of two above-ground floors. Behind the building, there is a large garden, which is a part of the property. Building is situated on a sloping terrain in a walking distance from a residential area of Šlapanice. There are two operating units: technical part (managemant part) and activity unit. Kindergarten is planed as a masonry building, based on strip foundations.
Kindergarten Domino
Keywords: Mateřská škola; zděný systém; jednoplášťová plochá střecha; křížem vyztužená deska; dvě nadzemní podlaží; betonové základové pasy; zateplovací systém ETICS; Kindergarten; masonry system; warm flat roof; two way slab; two above- ground floors; concrete strip foundation; external thermal insulation composite system (ETICS)